In vivo imaging of Lgr5-positive cell populations using confocal laser endomicroscopy during early colon tumorigenesis - Choi, Jin Woo; Kim, Jun Ki; Choi, Myunghwan; Kim, Yi Rang; Yun, Seok Hyun (Endoscopy, 2014)
Background and study aims: A diagnostic molecular marker for pre-neoplastic lesions, particularly before polyposis, is still lacking. Lgr5 has been broadly accepted as a marker for intestinal cancer stem cells. The aim of this study was to investigate the monitoring of Lgr5 +  cells as a useful tool for the early diagnosis of premalignant lesions before polyp formation.Methods: In vivo molecular imaging was performed to examine colon tumorigenesis in Lgr5-EGFP mice treated with azoxymethane and dextran sodium sulfate. eGFP + Lgr5 + regions in the descending colon were longitudinally monitored using side-view confocal endomicroscopy. Based on the eGFP signal intensity on the luminal surface, polyps were classified into two groups – Lgr5-high and Lgr5-low. White light colonoscopy was used to monitor polyp formation.Results: Approximately 75 % of the polyps originated from foci containing Lgr5-eGFP + cells, whereas 25 % of the polyps emerged from Lgr5 – foci. Among eGFP + foci, Lgr5-high foci grew faster than Lgr5-low foci. Conclusions: Polyps developed at Lgr5 + regions. Luminal Lgr5 expression was correlated with the growth rate of early-stage adenomas. Lgr5 is a promising molecular marker for the early diagnosis of colon tumors.